Interactive M-Learning Design Innovation using Android-Based Adobe Flash at WFH (Work From Home) - Voutama, Apriade; Maulana, Iqbal; ade, Nofri (Scientific Journal of Informatics, 2021)
Work From Home (WFH) is an activity that is carried out at home with the flexibility to work both place and time with the help of telecommunications technology. The birth of WFH was caused by the impact of the Covid-19 pandemic, which forced all activities in various fields, including government, business, trade, education, and so on, to be carried out online through the use of technology. One thing that is affected is in the field of education, the teaching and learning process must be carried out online. The problem that occurs is the unpreparedness of the infrastructure and resources in the smooth running of the distance learning process. One of the steps to provide convenience in the distance learning process is to innovate in the field of technology by creating an Android-based M-Learning application with an interactive concept so that it not only provides simple learning but is also designed attractively and interactively so that student participants can interact directly with this M-Learning application. Interactive M-Learning applications are designed with UML (Unified Modeling Language) modeling and translated into applications using Adobe Flash and then implemented on Android mobile devices.Â